A device for reducing the resistance of transom stern hulls. (1st September 2021) - Eslamdoost, Arash; Larsson, Lars; Brown, Matz
Abstract: A novel idea to reduce the resistance of a transom stern hull in displacement and semi-planing modes is investigated. By placing a spoon-shaped device in the recirculating zone behind the transom, the momentum of the forward-moving water will be absorbed, and a pushing force generated on the device. Numerical and experimental techniques are applied on a transom stern hull to optimize the shape and position of the device and to explore in detail the physics behind the gain. For the towed hull at a Froude number of 0.4, the maximum measured resistance reduction is 11%, while the computed maximum reduction is 17%. In self-propulsion with one propeller, the measured power reduction is 15%. The power cannot be computed with the applied propeller model, which is an axial body-force distribution in the propeller disk, but the reduction in thrust using the device is 11%. More significant gains are possible at smaller Froude numbers, while the effect is reduced at higher Froude numbers. Larger gains are achieved by splitting the thrust on two propellers. Highlights: Recirculating water behind transom stern hulls is considered as a source of energy loss. A Transom Pushing Device (TPD) is placed inside this region to reduce the loss. The performance of TPD has been verified using experimental and computation techniques. TPD reduced resistance more than 10% when the transom is not ventilated. TPD performance can be different in self-propulsion (higher gain might be achieved).